Health expenditure and economic development in low-and middle-income countries - Suhaila Saad,; Norashidah Mohamed Nor, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The purpose of this study is to examine whether health expenditure has any significant impact on economic development in low- and middle-income countries (LAMICs). We employed static panel data analysis involving 67 countries which were split into two groups: low-income countries and middle-income countries, and the time frame is spanning from 2010 to 2014. Both groups were analysed separately to measure the different impacts of health expenditure on the countries’ economic development. The results indicate a significant relationship between health expenditure and economic development for both groups of countries, whereby the impact was found to be slightly greater in middleincome countries compared to low-income countries. This finding denotes that the barrier for economic development in LAMICs is due to the considerably low allocation invested into health sectors, accompanied by the burden of many health-related problems. Therefore, strengthening the health sector by boosting health expenditure should be another priority in LAMICs to become developed countries.